2019
DOI: 10.1111/dom.13895
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the multiflorine‐derived substituted quinazolidine 55P0251 augments insulin secretion and lowers blood glucose via antagonism at α2‐adrenoceptors in mice

Abstract: Aims To investigate the mechanism of action of 55P0251, a novel multiflorine‐derived substituted quinazolidine that augments insulin release and lowers blood glucose in rodents, but does not act via mechanisms addressed by any antidiabetic agent in clinical use. Materials and Methods Using male mice, we determined the effects of 55P0251 on glucose tolerance, insulin secretion from isolated islets and blood oxygen saturation, including head‐to‐head comparison of 55P0251 to its inverted enantiomer 55P0250, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Accumulating evidence demonstrated that both diosgenin and multiflorenol exert anti-diabetic abilities (Table 2). Lehner et al 2020 There are several mechanisms how diosgenin and multiflorenol decrease the negative effects of diabetes mellitus. For example, diosgenin could reduce the activity of several biomarkers related to diabetes mellitus such as α-amylase, α-glucosidase (Ghosh et al 2014), andSGLT-1 (Al-Habori et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence demonstrated that both diosgenin and multiflorenol exert anti-diabetic abilities (Table 2). Lehner et al 2020 There are several mechanisms how diosgenin and multiflorenol decrease the negative effects of diabetes mellitus. For example, diosgenin could reduce the activity of several biomarkers related to diabetes mellitus such as α-amylase, α-glucosidase (Ghosh et al 2014), andSGLT-1 (Al-Habori et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Another important motivation for this effort is the desired biological activity that QAs have demonstrated in multiple studies [ 35 ]. Many QAs show beneficial and desired qualities such as antioxidant, antimicrobial, anti-carcinogenic, and anti-inflammatory activities [ 23 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. However, several individual alkaloids, especially sparteine, anagyrine, and cysteine, have undesired or even toxic activity, thus their concentrations in edible lupins must be strongly regulated [ 4 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, various alkaloids were found potentially effective against different diabetic models [24,25]. Quinolizidine alkaloids, such as lupanines, sparteine and multiflorine, beside their role in lowering the blood glucose, they have been associated with insulinotropic effects on isolated pancreatic islets [26]. Other alkaloids such as berberine, boldine and sanguinarine were found to have potential anti-diabetic activity [24].…”
Section: Anti-diabetic Effect Of Medicinal Plantsmentioning
confidence: 99%